Гамма каротажийн диаграммыг ашиглан нүүрсэн дэх ураны хэмжээг үнэлэх нь - Н, Норов; С, Даваа; Г, Хүүхэнхүү (Scientific transaction of the National University of Mongolia. Physics, 2022)
This paper discusses how estimating the uranium concentration on coal seam by the natural gamma ray togging curves of coal deposit.